1968
DOI: 10.7883/yoken1952.21.325
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Enteropathogenic, Facultatively Halophilic Bacteria, Vibrio Parahaemolyticus

Abstract: SUMMARY : In recent years, it was demonstrated that cultures of Vibrio parahaemolyticus isolated from human diarrheal stools were different from those from sea fish and sea water in a hemolytic activity on a special blood agar, which was named the Kanagawa phenomenon.In the present studies, the finding has been confirmed by using 3370 cultures of the vibrios. Ninety-six % of the vibrios isolated from human patients gave positive (hemolytic) reaction in the test of the phenomenon, while only one % of the vibrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
2
5

Year Published

1970
1970
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(152 citation statements)
references
References 6 publications
6
139
2
5
Order By: Relevance
“…By means of agglutination tests with specific 0 and K antisera, different serological types of V. parahaemolyticus may be recognized (Sakazaki, Iwanami & Tamura, 1968;Sakazaki, 1973). The serological classification is based on isolations from cases of human infection, and consequently the high proportion (31 %) of strains isolated in the survey which were not typable was to be expected (Table 5).…”
Section: Watermentioning
confidence: 99%
“…By means of agglutination tests with specific 0 and K antisera, different serological types of V. parahaemolyticus may be recognized (Sakazaki, Iwanami & Tamura, 1968;Sakazaki, 1973). The serological classification is based on isolations from cases of human infection, and consequently the high proportion (31 %) of strains isolated in the survey which were not typable was to be expected (Table 5).…”
Section: Watermentioning
confidence: 99%
“…However, strains isolated from environmental sources examined in this study, did not produce the toxin nor possess the toxin gene. As the TDH in V. parahaemolyticus is closely related to its enteropathogenicity [13,14], TDH-like toxin is estimated to be the enteropathogenicity factor in V. mimicus. Recently, Nishibuchi and colleagues [15] demonstrated that the TDH had enterotoxigenic activity and might be implicated in the watery diarrhoea by V. parahaemolyticus.…”
Section: Resultsmentioning
confidence: 99%
“…The cardinal taxonomic properties of V. parahaemolyticus are the following: catalase +, oxidase +, glucose attacked by a fermentative pathway, sucrose-, H2S from cysteine and thiosulphate -, indole +, nitrate +, urea-, gelatin+, arabinose +, growthin the presence of 10 % Na -Cl (Sakazaki et al 1968). In addition Baross & Liston (1968) observed that V. parahaemolyticus utilizes starch under anaerobic conditions in the presence of 5 % NaCl.…”
Section: Identification Proceduresmentioning
confidence: 99%
“…Epidemiological investigations carried out in Japan have demonstrated that the halotrophic Vibrio species V. parahaemolyticus can cause outbreaks of infectious enteritis when absorbed with food in great numbers (Sakazaki, Iwanami & Fukumi, 1963;Zen Yoji et al 1965;Sakazaki et al 1968). Such vibrios have their main habitat in estuarine waters, fish and shellfish.…”
Section: Introductionmentioning
confidence: 99%